2023
DOI: 10.1038/s43856-023-00244-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor DNA methylation is associated with exogenous oxytocin needs during parturition and postpartum hemorrhage

Abstract: Background The oxytocin receptor gene (OXTR) is regulated, in part, by DNA methylation. This mechanism has implications for uterine contractility during labor and for prevention or treatment of postpartum hemorrhage, an important contributor to global maternal morbidity and mortality. Methods We measured and compared the level of OXTR DNA methylation between matched blood and uterine myometrium to evaluate blood as an indicator of uterine methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 104 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…OT-R protein levels in venous and arterial blood from the umbilical cord may reveal differences in bi-directional OT-R traffic in normal, preterm and postterm deliveries. In that case, OT-R protein levels and epigenetic modifications [90] may lead to therapeutic interventions with exosomes [91] prepared, ideally, with the transmembrane orientation [12] of OT-R in villous exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…OT-R protein levels in venous and arterial blood from the umbilical cord may reveal differences in bi-directional OT-R traffic in normal, preterm and postterm deliveries. In that case, OT-R protein levels and epigenetic modifications [90] may lead to therapeutic interventions with exosomes [91] prepared, ideally, with the transmembrane orientation [12] of OT-R in villous exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…A pesquisa foi realizada nas bases de dados: Biblioteca Virtual de Saúde (BVS), Sciencedirect, PubMed, Periódicos CAPES, Biomed Central e Cochrane Library. Dessa maneira, obteve-se 355 resultados na BVS, que foram filtrados por: data de publicação (2020)(2021)(2022)(2023)(2024), tipo de estudo (retirada de revisões sistemáticas) e textos completosresultando em 85 artigos, sendo 3 selecionados. Na base Science Direct foram encontrados 3805 resultados, dos quais, após os filtros: "data de 2020-2024", retirada de "mini reviews" e de "review articles", foram encontrados 577 estudos para posterior leitura dos títulos e dos resumos, sendo escolhidos 6 ao final.…”
Section: Metodologiaunclassified
“…Over the next couple years, despite pandemic delays and challenges, with generous support from mentors, we were ultimately able to finish analyses and publish the findings of the postpartum hemorrhage case-control study. We demonstrated that not only was DNA methylation associated with greater oxytocin needs through labor and birth but that there was higher blood loss as well, but only in births where oxytocin was used in labor [ 51 ]. In a secondary study, we found that a commonly studied the single nucleotide polymorphism (rs53576) was also predictive of postpartum hemorrhage, particularly for those with less exposure to oxytocin during labor [ 52 ].…”
Section: Transition To a Deeper Understandingmentioning
confidence: 99%